Institutional and functional analysis of local councils executive bodies - Kovalenko , Nataliya (Theory and Practice of Public Administration, 2019)
The executive bodies of local councils, which are tasked with directly addressing a wide range of territorial development issues, are important to perform a wide range of public administration functions. Throughout the period of local self-government in Ukraine, the problems related to the lack of authority and lack of finance resources. So the article examines the institutional and functional conditions of activity organization in executive bodies of local councils.The purpose of the article is to substantiate the institutional and functional features of local government executive bodies in Ukraine.One of the main questions in organizing the activities of local councils executive bodies is to build their structural model based on the principle of abstraction, followed by the restoration of the structure through its meaningful filling. Next, consideration of the selected elements is necessary in order to identify the most significant ones in terms of the purpose and destination of the executive body itself. This approach will make possible to adequately identify the essence of local councils executive bodies as an institution of public administration.The activities of the local councils executive bodies are based on administrative principles, job identification, functional responsibilities, rights and authorities. In addition to models that reflect their place in the system of local self-government, the models of intra-structural organization (monolinear and multilinear) are considered and features of their application in modern conditions are defined.It is proved that the executive bodies of local councils at the present period are management structures characterized by such features as complexity and functional specialization. It is noted that for the formation of effective public administration at the local level, it is necessary to ensure openness of the organizational structure for community participation.